The mechanical properties of nylon 6 (pa6)/acrylonitrile-butadiene-styrene (ABS) blends - Arsad, Agus; Hassan, Azman; Mohd. Idris, Mohd. Nizam; Rahmat, Abdul Razak (2006)
Blending is a combination of two or more polymer to produce a new polymer which has good mechanical properties at low cost. Nylon 6 and ABS both have their specialty and weakness but on the other hand, with the combination of Nylon/ABS, it helps to patch both weaknesses. For this study, high impact ABS was used to blend with PA 6 to improve the mechanical properties and to reduce the cost. The main purpose of this study was to investigate the ratio of PA 6/ABS blends to produce a good combination of mechanical properties such as tensile, flexural and impact properties. Besides, the study was also investigate the compatibility of PA 6/ABS and to examine the structure morphology of its blends. For sample preparation, the pellets of PA 6 and ABS were extruded at the different composition using twin screw extruder and then being moulded using injection moulding machine. In this study, the tests conducted were tensile test, flexural test, Izod impact test and morphology examination of PA 6/ABS blends. With the increasing of ABS content in PA 6/ABS blend, the tensile strength, tensile modulus and elongation at break were decreased. Besides, the flexural strength and flexural modulus of the blend were also decreased. However, the addition of ABS increased the Izod impact strength of the blend. The best ratio for the PA 6/ABS blends based on the mechanical properties is 60:40 PA 6/ABS.